Ecological Validity of Expressed Emotion in Early Psychosis - Hinojosa-Marqués, Lídia; Domínguez-Martínez, Tecelli; Kwapil, Thomas R.; Barrantes-Vidal, Neus (Frontiers in Psychiatry, 2019)
Expressed Emotion (EE) is an aspect of the family environment that influences the course of multiple forms of psychopathology. However, there is limited research about how EE dimensions [i.e., criticism and Emotional Over-Involvement (EOI)] are expressed in real-world settings. The present study used experience sampling methodology to investigate: (1) the criterion and construct validity of daily-life, momentary measures of criticism and EOI, and (2) the construct and ecological validity of psychometric EE-dimensions as assessed with the self-report Family Questionnaire (FQ). A total sample of 55 relatives (34 relatives of At-Risk Mental State patients and 21 of First-Episode Psychosis patients) were prompted randomly six times daily for 1-week to assess their current emotional experiences and cognitive appraisals. Relatives also completed the FQ. Momentary criticism and EOI were significantly associated with the two FQ-EE dimensions respectively, supporting the criterion validity of real-world assessed EE dimensions. As hypothesized, momentary and FQ-EE dimensions were associated with decreased positive affect, as well as with appraisals of less effective coping in daily life. Only momentary EE dimensions were associated with increased momentary negative affect. Partly in contrast with our hypotheses, momentary criticism and FQ-criticism were more consistently related to situational stress and burden than momentary EOI and FQ-EOI. Finally, neither momentary nor FQ-EE dimensions showed distinct patterns of associations with illness attributions. Findings partly support the construct validity of momentary criticism and EOI as well as the construct and ecological validity of the FQ as a sensitive measure of EE dimensions.